PENGARUH KARAKTERISTIK INDIVIDU DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DI MULYA MITRA COLLEGE - Feriandy Feriandy (Aliansi : Jurnal Manajemen dan Bisnis, 2019)
Effect of Individual Characteristics and Organizational Culture on Employee Performance at Mulya Mitra College. The existence of humans as resources is very important in an educational institution, because human resources are a support that is realized through work, talent, creativity, encouragement and real role. Without the quality of human resources, the educational institution would not be able to move and achieve the vision it wants. Factors affecting employee performance are Individual Characteristics and Organizational Culture. The purpose of this study is to look for empirical evidence of the influence of Individual Characteristics and Organizational Culture on Employee Performance at Mulya Mitra College. This type of research uses census methods that discuss the effect of Individual Characteristics and Organizational Culture on Employee Performance. The study population was employees at Mulya Mitra College. The sampling method uses stratified-proportional random sampling with the number of samples taken from the total population of 40 people. Methods of data analysis using descriptive and statistical analysis techniques include multiple regression analysis, hypothesis testing with simultaneous test or F test, hypothesis testing with partial test or t-test and analysis of the coefficient of multiple determination. The results of the study concluded that Individual Characteristics and Organizational Culture simultaneously had a significant positive effect on performance. This is indicated by the p-value of all the independent variables 0.05. Individual characteristics and organizational culture partially also have a significant positive effect on performance. This is indicated by p-value 0.05.